The Role of School Administration Personnel In Improving School Services - Arianti, Novia Putri; Nurabadi, Ahmad; Juharyanto, Juharyanto (Proceedings Series of Educational Studies, 2024)
This study aims to examine the role of school administration personnel (TAS) competencies in improving school services. TAS competencies include technical, managerial, interpersonal, and professional abilities. Through the literature study method, this study reveals that mastery of information technology and effective communication skills are the key to the success of administrative services in schools. Adequate TAS competencies not only improve the operational efficiency of the school but also contribute to the positive image of the school and the satisfaction of the parties involved. Therefore, the continuous development of TAS competencies is very important to support the achievement of educational goals. TAS competence is a key factor in elevating school services and ultimately achieving educational success.